Mapping neutron biological effectiveness for DNA damage induction as a function of incident energy and depth in a human sized phantom - Mentana, Alice; Quaresima, Virgilio; Kundrát, Pavel; Guardamagna, Isabella; Lonati, Leonardo; Iaria, Ombretta; Previtali, Andrea; Amantini, Giorgia Santi; Lunati, Luca; Boretti, Virginia; Narici, Livio; Di Fino, Luca; et al. (Scientific reports, 2025)
We present new developments for an ab-initio model of the neutron relative biological effectiveness (RBE) in inducing specific classes of DNA damage. RBE is evaluated as a function of the incident neutron energy and of the depth inside a human-sized reference spherical phantom. The adopted mechanistic approach traces neutron RBE back to its origin, i.e. neutron physical interactions with biological tissues. To this aim, we combined the simulation of radiation transport through biological matter, performed with the Monte Carlo code PHITS, and the prediction of DNA damage using analytical formulas, which ground on a large database of biophysical radiation track structure simulations performed with the code PARTRAC. In particular, two classes of DNA damage were considered: sites and clusters of double-strand breaks (DSBs), which are known to be correlated with cell fate following radiation exposure. Within a coherent modelling framework, this approach tackles the variation of neutron RBE in a wide energy range, from thermal neutrons to neutrons of hundreds of GeV, and reproduces effects related to depth in the human-sized receptor, as well as to the receptor size itself. Besides providing a better mechanistic understanding of neutron biological effectiveness, the new model can support better-informed decisions for radiation protection: indeed, current neutron weighting (ICRP)/quality (U.S. NRC) factors might be insufficient for use in some radiation protection applications, because they do not account for depth. RBE predictions obtained with the reported model were successfully compared to the currently adopted radiation protection standards when the depth information is not relevant (at the shallowest depth in the phantom or for very high energy neutrons). However, our results demonstrate that great care is needed when applying weighting factors as a function of incident neutron energy only, not explicitly considering RBE variation in the target. Finally, to facilitate the use of our results, we propose look-up RBE tables, explicitly considering the depth variable, and an analytical representation of the maximal RBE vs. neutron energy.
Keywords: Phantoms, Imaging; poškození DNA; Relative Biological Effectiveness; DNA Damage; metoda Monte Carlo; fantomy radiodiagnostické; dvouřetězcové zlomy DNA; Humans; lidé; neutrony; DNA Breaks, Double-Stranded; Neutrons; relativní biologická účinnost; Monte Carlo Method